1999
DOI: 10.1006/jcph.1999.6316
|View full text |Cite
|
Sign up to set email alerts
|

A Consistent Hybrid Finite-Volume/Particle Method for the PDF Equations of Turbulent Reactive Flows

Abstract: The paper describes a new hybrid finite-volume (FV)/particle method developed for the solution of the PDF equations for statistically stationary turbulent reactive flows. In this approach, the conservation equations for mean mass, momentum, and energy conservation are solved by a FV method while a particle algorithm is employed to solve the fluctuating velocity-turbulence frequency-compositions joint PDF transport equation. The mean velocity and pressure are supplied to the particle code by the FV code which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 30 publications
3
143
0
1
Order By: Relevance
“…(d) It has been found that it is important to ensure that the turbulence Eulerian model and the Lagrangian one are as consistent as possible 38,49 . The lack of consistency may also lead to unphysical results, at least for the limit case of very small particles 38 .…”
Section: A Mean Fluid Value Predictionsmentioning
confidence: 99%
“…(d) It has been found that it is important to ensure that the turbulence Eulerian model and the Lagrangian one are as consistent as possible 38,49 . The lack of consistency may also lead to unphysical results, at least for the limit case of very small particles 38 .…”
Section: A Mean Fluid Value Predictionsmentioning
confidence: 99%
“…However, the two most popular approaches (Eulerian and Lagrangian) for two-phase flow modelling have disadvantages which limit their capacities. Hybrid methods try to gather the advantages of the Eulerian approach (expected values free from statistical error and low calculation costs) with those of the Lagrangian approach (polydispersity and non-linear local source terms are treated without approximations) [31,32]. At the moment, most hybrid methods use only one description (Eulerian or Lagrangian) for each phase.…”
Section: Appendix C On Hybrid Modelling Of Dispersed Turbulent Two-pmentioning
confidence: 99%
“…This approach, which will be referred to as A1, relies on the combined use of relaxation-type techniques [1,4,5,9,12,13,28,35,36,38] and upwinding schemes [14,19,22,23,29,30] and was first introduced in [25] in order to predict single-phase turbulent flows [32]. In the latter approach, an extended hyperbolic system was introduced in a natural way, following what is done for previous associated Eulerian models (see [2,3,6,21]).…”
Section: Introductionmentioning
confidence: 99%
“…A good overview of the different models can be found in [17]. In the work presented here a joint PDF of velocity and composition vector is employed.…”
Section: Joint Pdf Modelmentioning
confidence: 99%
“…One possibility is to couple the particle method with an ordinary finite-volume or finite-difference solver to obtain the mean pressure field from the Navier-Stokes equations. These so called hybrid PDF/CFD methods are widely used by different authors for many types of flames [15,16,17,18,19,20]. In the presented paper a hybrid scheme is presented and used as well.…”
Section: Introductionmentioning
confidence: 99%